Ferula ferulaeoides ethyl acetate extract induces apoptosis in esophageal cancer cells via mitochondrial and PI3K/Akt/Bad pathways - Yerlan Bahetjan; Wenqi Liu; Muguli Muhaxi; Ni Zheng; Fatemeh Sefidkon; Kejian Pang; Guangwen Shu; Xinzhou Yang (Arabian Journal of Chemistry, 2023)
Background: Ferula ferulaeoides (Steud.) Korovin is a traditional ethnopharmacological plant used for lump elimination and as a spice, especially in places like India. It has also been employed in the livestock and food industries. This investigation aimed to explore the anti-tumor mechanisms of ethyl acetate extract fractions of dried roots of Ferula ferulaeoides (FF-EtOAc) on esophageal cancer (EC) cells. Furthermore, it was hypothesized that FF-EtOAc could inhibit EC cells growths by inducing apoptosis. Results: In a time- and dose-dependent manner, FF-EtOAc considerably reduced the number of migrating EC cells. And FF-EtOAc also inhibited the growth of EC cells in vivo, and it is less toxic to nude mice. In terms of the FF-EtOAc anticancer mechanism, the findings revealed that FF-EtOAc inhibited EC cells growth by activating mitochondrial signaling pathways and PI3K/Akt/Bad signaling pathways. Conclusions: Through both in vitro and in vivo experiments, FF-EtOAc significantly exhibited anti-esophageal cancer activity. The anti-EC activity of FF-EtOAc may be due to the activation of the mitochondrial apoptotic and PI3K/Akt/Bad signaling pathways.